Realitas yang Sakral: Upacara Sedekah Gunung Merapi dalam Perspektif Mircea Eliade - Muhammad Akbar; Naufal Ridhwan Aly (Kawalu: Journal of Local Culture, 2019)
Upacara Sedekah Gunung Merapi is a form of ritual that still exists by residents of Lencoh Village, Selo District, Boyolali Regency. This ceremony is a ritual tradition that is held every year, to be precise at 1 Muharram to welcome the Islamic New Year. This paper seeks to elaborate Mircea Eliade's thoughts in the case of Upacara Sedekah Gunung Merapi, to be precise in Lencoh Village, Selo District, Boyolali Regency. This ceremony is a ritual held to give offerings to the spirits of deceased ancestors who when they were still alive were believed by the villagers to be the forerunners of the village founders. Also, this ceremony is an expression of gratitude addressed to God. The procession of Upacara Sedekah Gunung Merapi begins with an offering ceremony in the form of ndas kebo, tumpeng, and other uba rampe as a complement to the offerings. The offerings will be floated in the crater of Mount Merapi. Each of the offerings in this ceremony has its meaning for local. This research is expected to provide information about the meaning of Upacara Sedekah Gunung Merapi as well as to explore local wisdom studies in Indonesia using the perspective of Mircea Eliade's thinking.